The Multicultural School. Analysis of challenges and opportunities based on examples from Vasa Övningsskola - Adamczewski, Jakub (Biuletyn Historii Wychowania, 2017)
The aim of this article is to present a discussion on the phenomenon of multicultural schools in Finland. The author will present both challenges and opportunities of multiculturalism based on examples from Vasa Övningsskola. The article will present a brief history of multicultural schools in the world and explain the roots of multicultural education. The purpose of this article is to explore new ideas and solutions for multicultural schools based on the best educational system in the world.